Association between parenting styles and the role of Peruvian adolescents in bullying, 2019 - Zegarra Chapoñan, Roberto; Zeladita Huaman, Jhon Alex; Cuba Sancho, Juana Matilde; Castillo Parra, Henry; Moran Paredes, Gladys Ivonne; Cárdenas Niño, Lucila (Revista Cuidarte, 2022)
Introduction: Parenting styles determine child behavior; however, there is little information on their impact on bullying. Objective: To determine the association between different parenting styles and the role assumed in bullying, as well as to identify adolescents’ profiles according to their involvement in bullying. Materials and Methods: A cross-sectional analytical study was conducted in Lima, Peru, in 2019. The Steinberg’s Parenting Styles Scale and the European Bullying Intervention Project Questionnaire (EBIP-Q) were administered to 563 students from public schools. Scores were obtained by confirmatory factor analysis. Spearman’s correlation coefficient, Pearson’s Chi-square test, and multinomial logistic regression analysis were used. Results: There is an association between parenting styles and adolescents’ role in bullying. The multivariate analysis reported that being male was associated with the role of the bully (OR: 2.73; 95% CI 1.59–4.68), while access to social media (OR: 2.23; CI 95% 1.11–4.49), being male (OR: 1.75; CI=1.06–2.88), and parenting styles (neglectful [OR: 2.72; 95% CI 1.32–5.59] and mixed [OR: 0.38; 95% CI 0.16–0.91] compared to authoritarian parenting style) were predictors of the role of the victimized bully. Discussion: The association found in the study confirms previous findings; however, it opens the debate on the influence of neglectful parenting style on bullying dynamics. Conclusions: Both neglectful and authoritarian parenting styles (lower proportion) have a positive and significant effect on the role of victimized bully.How to cite this article: Zegarra Chapoñan Roberto, Zeladita Huaman Jhon Alex, Cuba Sancho Juana Matilde, Castillo Parra Henry, Moran Paredes Gladys Ivonne, Cárdenas Niño Lucila. Asociación entre los estilos de crianza y el rol de los adolescentes peruanos en el acoso escolar, 2019. Revista Cuidarte. 2023;14(1):e2679.  http://dx.doi.org/10.15649/cuidarte.2679
Keywords: Adolescent; Bullying; Child Rearing; Students